Cardiac structure and inflammation drive memory impairment via dual pathways of heart-brain axis dysregulation in atrial fibrillation patients undergoing catheter ablation - Chen, Xin; Ni, Jie; Wang, Yu; Kou, Dandan; Ge, Danni; Xue, Xunwen; Zhao, Yingming; Xu, Biao; Li, Ming; Chen, Jiu (Frontiers in Neuroscience, 2025)
BackgroundAtrial fibrillation (AF) patients undergoing catheter ablation (CA) frequently present with cardiac structural and functional alterations and persistent memory impairment. This study aimed to investigate how cardiac structure and function impacts memory-related brain structure and function, whether CA reverses impaired memory networks, and to delineate the dual-pathway regulatory mechanism of the heart-brain axis underlying AF-associated memory deficits.MethodsThirty-eight AF patients underwent longitudinal assessments [memory function tests, clinical evaluations including blood biomarkers and cardiac function, structural/functional magnetic resonance imaging (MRI)] before CA and on postoperative day 7. Forty-five healthy controls (CN) were included for comparison. Hippocampal functional connectivity (FC) and voxel-based morphometry were used to quantify memory-related brain networks and gray matter (GM) volume. Bivariate correlations explored relationships between GM alterations, hippocampal FC, memory performance, and clinical features (cardiac structural parameters and blood-borne inflammatory markers).ResultsFirst, compared with CN, AF patients showed memory impairment, reduced GM volume in the bilateral calcarine cortex, cuneus, lingual gyrus, inferior/middle temporal gyri, and left fusiform gyrus, and increased hippocampal FC with the bilateral middle frontal gyrus, insula, Rolandic operculum, left inferior frontal gyrus (opercular/orbital/triangular parts), and right postcentral/supramarginal/superior temporal gyri. Second, left ventricular end-diastolic diameter (LVDd) was positively associated with GM volume in the left middle temporal gyrus (MTG.L, p = 0.016), right inferior temporal gyrus (p = 0.006), and left cuneus (p = 0.026); MTG.L GM volume correlated positively with Auditory Verbal Learning Test (AVLT)-Recall scores (p = 0.044), while hippocampal FC with the right postcentral gyrus correlated negatively with both inflammatory markers (PCT, p = 0.010) and AVLT-Delayed Recall (20 min) scores (p = 0.013). Third, post catheter ablation (post-CA), AF patients exhibited increased hippocampal FC with the right middle frontal gyrus, right midcingulate cortex, and left superior frontal gyrus, and decreased FC with the right lingual gyrus and calcarine cortex.ConclusionCardiac structural parameters (LVDd) associate with memory-related brain atrophy, whereas blood-borne inflammatory markers link to hippocampal memory network dysregulation—two distinct pathways driving AF-related memory impairment. These findings clarify the dual-pathway regulatory mechanism of the heart-brain axis, offering novel insights into AF-associated cognitive dysfunction and potential CA-mediated memory recovery.